Analysis of Infants Cries - Indira Nandyal (Journal of All India Institute of Speech and Hearing, 1970)
'During infancy, the child's only mode of communication is the cry and we should listen to his vocalization and try to interpret it. When a ttaby is ill, the parents, too, are most eager and anxious to have some explanation of his prognosis and possible life-long defects.  Any method which could provide further enlightenment should be thoroughly explored' (Siruio and Michelsson, 1976).